"Clearly they are in the circle of care, but . . .": A qualitative study exploring perceptions of personal health information sharing with community pharmacists in an integrated care model. (November 2020) - Rolf von den Baumen, Teagan; Lake, Jennifer; Everall, Amanda C.; Dainty, Katie; Rosenberg-Yunger, Zahava; Guilcher, Sara J. T.
Background: Ontario's Health Links approach to care is an integrated care model designed to optimize care for patients with complex needs. Currently, community pharmacists have no formalized role. This study aimed to explore stakeholders' perceptions about privacy and its impact on community pharmacists' involvement with integrated care models. Methods: A qualitative study using semistructured telephone-based interviews was conducted. Participants worked in Ontario as pharmacists, providers in Health Links or team-based models or decision-makers in Health Links or health regions. Thematic analysis followed the Qualitative Analysis Guide of Leuven. Results: Twenty-two participants were interviewed, and all but one commented on privacy or information sharing in integrating community pharmacists with integrated care models. The 4 themes identified were as follows: 1) what does the circle of care look like? 2) value of sharing information, 3) uncertainty of what information to share and 4) perceptions on how to share information. Interpretation: The concerns surrounding privacy of personal health information and who is included in the circle of care represented an important barrier for integration. Enablers to mitigate privacy concerns included relationship building between community pharmacists, patients and other health care professionals and mutual access to information-sharing platforms such as electronic health records. Conclusion: Providers' and decision-makers' perceptions about community pharmacists and privacy affect information sharing and are incongruent with Ontario's Personal Health Information Protection Act. Education is needed for health care professionals on legislation, especially as health systems move towards integrated care models to improve care. Can Pharm J (Ott) 2020;153:xx-xx.